Physics Contributions Effect of using different U/S probe Standoff materials in image geometry for interventional procedures: the example of prostate - Diamantopoulos, Stefanos; Milickovic, Natasa; Butt, Saeed; Katsilieri, Zaira; Kefala, Vasiliki; Zogal, Pawel; Sakas, George; Baltas, Dimos (Journal of Contemporary Brachytherapy, 2011)
Purpose : This study investigates the distortion of geometry of catheters and anatomy in acquired U/S images, caused by utilizing various stand-off materials for covering a transrectal bi-planar ultrasound probe in HDR and LDR prostate brachytherapy, biopsy and other interventional procedures. Furthermore, an evaluation of currently established water-bath based quality assurance (QA) procedures is presented. Material and methods: Image acquisitions of an ultrasound QA setup were carried out at 5 MHz and 7 MHz. The U/S probe was covered by EA 4015 Silicone Standoff kit, or UA0059 Endocavity balloon filled either with water or one of the following: 40 ml of Endosgel®, Instillagel®, Ultraschall gel or Space OAR™ gel. The differences between images were recorded. Consequently, the dosimetric impact of the observed image distortion was investigated, using a tissue equivalent ultrasound prostate phantom – Model number 053 (CIRS Inc., Norfolk, VA, USA). Results: By using the EA 4015 Silicone Standoff kit in normal water with sound speed of 1525 m/s, a 3 mm needle shift was observed. The expansion of objects appeared in radial direction. The shift deforms also the PTV (prostate in our case) and other organs at risk (OARs) in the same way leading to overestimation of volume and underestimation of the dose. On the other hand, Instillagel® and Space OAR™ “shrinks” objects in an ultrasound image for 0.65 mm and 0.40 mm, respectively. Conclusions : The use of EA 4015 Silicone Standoff kit for image acquisition, leads to erroneous contouring of PTV and OARs and reconstruction and placement of catheters, which results to incorrect dose calculation during prostate brachytherapy. Moreover, the reliability of QA procedures lies mostly in the right temperature of the water used for accurate simulation of real conditions of transrectal ultrasound imaging.